The Effect of Emotion Change Puzzle Media on Visual-Spatial Intelligence for Early Childhood Education - Mubaroroh, Arini; Hidayah, Nur; Pramono, Pramono (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2022)
Purpose – This study aims to determine the effect of emotion change puzzle media on visual-spatial intelligence in children aged 5-6 years at TK ABA 39 Malang City.Design/methods/approach – The method used in this study is an experimental method using a pre-experimental design by choosing an Intact-Group Comparison design. The research subjects totaled 30 children who were children aged 5-6 years in TK ABA 39 Malang City. The Analysis used in this study is a normality test, homogeneity test, and hypothesis test.Findings – The results of data analysis, and the validity test obtained. The validity test obtained the tcount test 0.053 ≥ from ttable -0.601 which means there is an increase in visual-spatial intelligence in children aged 5-6 years. The standard value of the post-test results is higher than the standard value of the post-test results, namely the experimental pre-test 7.12, pre-test control 7.38, experimental post-test 10.79, and the control post-test 10.26.Research implications/limitations – This study concluded that the emotion change puzzle media has a significant influence on the visual-spatial intelligence of children aged 5-6 years in TK ABA 39 Malang City.Practical implications – The results show that using media emotion change puzzle to children’s learning media can be done by watching animated videos telling stories about various kinds of expressions.Originality/value – This study highlight that emotion change puzzle media can be alternative learning tools that improve children’s visual-spatial intelligence.Paper type: Research paper